2015
DOI: 10.1128/aac.03906-14
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Injectable, Long-Acting Nevirapine for HIV Prophylaxis in Breastfeeding Infants

Abstract: c Mother-to-child transmission (MTCT) of HIV-1 remains a global health problem. The World Health Organization (WHO) recommendations advise the administration of a once-daily, oral, prophylactic regimen of the nonnucleoside reverse transcriptase inhibitor nevirapine (NVP) from birth until 4 to 6 weeks of age for infants born to HIV-infected mothers in regions without access to safe and nutritionally adequate alternatives to breast milk. A critical factor driving the successful implementation of the WHO guidelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Nanoparticle based systems are readily taken up by cells and disseminated into tissues to form drug depots at these sites for subsequent slow release 20 . Other controlled release injection site drug depot formulations include microparticle carrier systems 21 , 22 . However, microparticles tend to aggregate limiting their usage due to lack of particle homogeneity, leading to injection site reactions 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticle based systems are readily taken up by cells and disseminated into tissues to form drug depots at these sites for subsequent slow release 20 . Other controlled release injection site drug depot formulations include microparticle carrier systems 21 , 22 . However, microparticles tend to aggregate limiting their usage due to lack of particle homogeneity, leading to injection site reactions 23 .…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported on a novel approach to achieve parenteral sustained-release ARV delivery based on large (Ͼ50 m), monodisperse drug particles coated with biocompatible polymers that control the compound's release kinetics (21) and have used it to develop long-acting injectable formulations of the NNRTI nevirapine (LA-NVP). Pharmacokinetic (PK) modeling showed that LA-NVP holds promise as a prophylactic in mother-to-child transmission of HIV-1, providing 6 weeks of protective plasma drug levels in the HIV-1-negative infant from a single subcutane-ous injection at birth (21).…”
mentioning
confidence: 99%
“…Pharmacokinetic (PK) modeling showed that LA-NVP holds promise as a prophylactic in mother-to-child transmission of HIV-1, providing 6 weeks of protective plasma drug levels in the HIV-1-negative infant from a single subcutane-ous injection at birth (21). Unfortunately, preliminary studies using large TAF crystals coated with the blocking polymer poly(D,Llactic acid) did not sufficiently slow the in vitro release rate for a viable sustained-release candidate in HIV-1 PrEP, where a dosing interval of 1 month or longer typically is required.…”
mentioning
confidence: 99%
“…As a proof-of-concept, it has been shown that flagellin of which the hypervariable region is removed can be used to activate TLR5 without triggering an inflammation reaction [ 66 ]. This was further applied in a murine infection model, and evidence for therapeutic synergy between antibiotics and flagellin in the context of pneumonia was obtained [ 67 , 68 , 69 ]. Based on these data, FAIR continues to generate PK, PD, and toxicology data in in vitro systems and preclinical species in order to develop flagellin towards clinical use as an add-on to the standard of care with antibiotics [ 70 ].…”
Section: The Fair Projectmentioning
confidence: 99%